2019
DOI: 10.1111/cxo.12818
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold diode micropulse laser versus observation in acute central serous chorioretinopathy

Abstract: SDM laser produces faster and superior visual rehabilitation without any adverse effects. It also reduces the chances of CSC going into chronicity and recurrence compared to the current standard of care (observation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
5
28
0
2
Order By: Relevance
“…A significant reduction in SRF volume was observed already during the first 3 months. This is consistent with previous studies reporting the applicability of subthreshold laser treatment in acute CSC [7,35,36] for providing a faster visual rehabilitation than the standard of care (observation).…”
Section: Discussionsupporting
confidence: 92%
“…A significant reduction in SRF volume was observed already during the first 3 months. This is consistent with previous studies reporting the applicability of subthreshold laser treatment in acute CSC [7,35,36] for providing a faster visual rehabilitation than the standard of care (observation).…”
Section: Discussionsupporting
confidence: 92%
“…Other methods, such as intravitreal injection of anti-VEGF medications appeared to be unsuccessful in treating pure serous chorioretinopathy [37,55]. Oral mineralocorticoid pathway inhibitors are used as a support of invasive therapies; however, so far, there has been no consent regarding their efficacy in the treatment of chronic CSCR [27,56,57,58].…”
Section: Smplt In Cscrmentioning
confidence: 99%
“…However, with the advent of SMPLT, ophthalmologists have a safe, non-damaging tool to the retina for the treatment of CSCR. Arora et al compared the results of early treatment of CSCR with observation [58]. Patients who undergone SMPLT in the acute phase of CSCR had better final BCVA and better contrast sensitivity than the patients that were just observed.…”
Section: Smplt In Cscrmentioning
confidence: 99%
“…Arora et al showed that patients with acute CSCR in whom prompt SMPLT treatment was administered had better final BCVA and contrast sensitivity in comparison with patients with acute CSCR who were observed only. [52] Definitely, more research is needed to provide new recommendations for the treatment of both acute CSCR and chronic CSCR. It would be useful to more precisely indicate the position of SMPLT and photodynamic therapy (PDT) in the treatment of this disease, as these two methods are the most promising and seem to provide the best functional and morphological results.…”
Section: Discussionmentioning
confidence: 99%